Modeling the role of perceived green value and consumer innovativeness in green products’ consumption intention within the theory of planned behavior - Eunice Kagure Muraguri; Sun Jin; Amadou Samake (Sustinere: Journal of Environment and Sustainability, 2020)
Sustainable consumption is on the rise, however scarce literature exists to explain the consumers’ perceived green value of green home apparel in the Chinese context. This study while applying the Theory of Planned Behavior (TPB) explores consumers’ intention to consume green products guided by Perceived Green Value (PGV) dimensions of utilitarian value, environmental value and hedonic value through a study of electric home appliances in China. The key findings established from a survey of 426 students in Beijing – China reveal a positive significant relationship between the three green value dimensions and the TPB factors’ of attitude, subjective norms and perceived behavioral control. The relationship was however strongest between the three dimensions and attitude. Further, the relationship between TPB factors and intention to consume green products was significantly positive. In addition, consumer innovativeness positively moderated the relationship between the three PGV dimensions and attitude. The discussion and conclusion outlines the theoretical implications and the value dimensions for marketing practitioners and policy makers to focus on in order to enjoy long term business sustained success. The scholars acknowledge the study limitations and offer research directions for future studies.